2012
DOI: 10.1039/c2jm16569d
|View full text |Cite
|
Sign up to set email alerts
|

Facile and green synthesis of well-dispersed Au nanoparticles in PAN nanofibers by tea polyphenols

Abstract: The green natural compounds, tea polyphenols (TP), were introduced to synthesize well-dispersed Au nanoparticles (AuNPs) in polyacrylonitrile (PAN) nanofibers by combining an in situ reduction approach and electrospinning technique. The AuNPs were firstly synthesized in aqueous solution to test the reducibility of the TP. Then, the well-dispersed AuNPs in PAN nanofibers were obtained by an in situ reduction approach and electrospinning technique. Fourier transform infrared spectroscopy (FTIR) was utilized to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 45 publications
1
56
0
Order By: Relevance
“…2). Our previous work found that as consists of multiple hydroxyls, TP can chelate with the Ag ions and the chelated Ag ions can be reduced into Ag 0 atoms in situ, contributing to forming smaller and uniform AgNPs [39]. It is believed that the prepared AgNPs in the present approach were mainly reduced by TP, which will be discussed in the following work.…”
Section: Resultsmentioning
confidence: 78%
“…2). Our previous work found that as consists of multiple hydroxyls, TP can chelate with the Ag ions and the chelated Ag ions can be reduced into Ag 0 atoms in situ, contributing to forming smaller and uniform AgNPs [39]. It is believed that the prepared AgNPs in the present approach were mainly reduced by TP, which will be discussed in the following work.…”
Section: Resultsmentioning
confidence: 78%
“…Pyrrolic N is found to be 29% of total N content in CN x /PAN/CB/Nafion ® nanofibers. The presence of peak in CN x /PAN/CB/Nafion ® nanofibers at 391.1 eV is attributed to nitrile peak [24]. Nitrile N content is found to be 25% out of total N content in CN x /PAN/CB/ Nafion ® nanofibers.…”
Section: Scanning Electrochemical Microscopymentioning
confidence: 93%
“…[35][36][37] Polyphenols such as EGCG demonstrated to be efficient ligands for metal ions and multiple phenolic hydroxyls are able to bind Au 3+ ions by forming stable chelating rings. As a consequence of complexation, a redox reaction occurs, and the chelated Au 3+ ions are reduced to Au 0 atoms in situ, while a part of the phenolic hydroxyls is simultaneously oxidized to corresponding quinone.…”
Section: Introductionmentioning
confidence: 99%